Decentralization of firms in a country with weak institutions: Evidence from Russia - Irina Levina (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2018)
Can decentralization of firms be successful in an environment with weak institutions? Decentralization can do a great job for improving firms' efficiency and competitiveness by creating opportunities for quicker and more competent decision-making and enhancing motivation of employees. However, decentralization is associated with a substantial increase in agency risk, which is particularly important for firms that operate under weak institutions. Hence, the popular belief is that in countries with weak institutions, firms are unable to successfully decentralize. In this paper, we study evidence from Russian firms to challenge this belief. Following anecdotal evidence and trends observed in the data, we introduce the notions of real decentralization for firms that decentralize decision-making to competitively hired professionals and cautious decentralization for firms that decentralize to people hired through connections. We demonstrate that really decentralized firms are, on average, significantly more likely to invest even in Russian weak institutional conditions. We also show that the gap in investment between really decentralized and other firms declines as corruption grows. Empirical research presented in the paper implies that there still can be significant room for decentralization even in an environment with weak institutions, such as that of Russia. However, as the role of non-market factors (such as corruption) in firms' prosperity increases, the potential value of decentralization for the firms declines.
urn:nbn:de:101:1-2019040811072298329389
Keywords: D02; D22; D23; L2; M2; M51; 330; decentralization; decision-making; investment; institutions; corruption; Russia